2019
DOI: 10.3390/ma12244149
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Selected Carbon Nanostructures on the CYP2C9 Enzyme of the P450 Cytochrome

Abstract: Carbon nanostructures have recently gained significant interest from scientists due to their unique physicochemical properties and low toxicity. They can accumulate in the liver, which is the main expression site of cytochrome P450 (CYP450) enzymes. These enzymes play an important role in the metabolism of exogenous compounds, such as drugs and xenobiotics. Altered activity or expression of CYP450 enzymes may lead to adverse drug effects and toxicity. The objective of this study was to evaluate the influence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…On the other hand, the results obtained from the ATP assay suggested a high toxic effect in all groups, starting from the lowest used concentration ( Figure 7 ). Interestingly, the highest cytotoxic effect was observed for GO, while oxidized forms of graphene are generally more biocompatible, and GO had a low toxic effect against other cell lines, such as liver-derived cells, in our previous studies [ 23 , 39 ]. Furthermore, natural graphene or reduced forms of graphene oxides exhibited not only a cytotoxic effect against other cancer cells [ 17 , 40 ], but also more hemolytic character when compared to GO [ 41 ].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…On the other hand, the results obtained from the ATP assay suggested a high toxic effect in all groups, starting from the lowest used concentration ( Figure 7 ). Interestingly, the highest cytotoxic effect was observed for GO, while oxidized forms of graphene are generally more biocompatible, and GO had a low toxic effect against other cell lines, such as liver-derived cells, in our previous studies [ 23 , 39 ]. Furthermore, natural graphene or reduced forms of graphene oxides exhibited not only a cytotoxic effect against other cancer cells [ 17 , 40 ], but also more hemolytic character when compared to GO [ 41 ].…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, natural graphene or reduced forms of graphene oxides exhibited not only a cytotoxic effect against other cancer cells [ 17 , 40 ], but also more hemolytic character when compared to GO [ 41 ]. However, it was also found that GO and other carbon nanostructures, such as carbon nanotubes, might non-specifically inhibit enzymatic reactions by binding to the structure of a protein [ 24 , 39 , 42 ]. Considering the nature of the ATP assay, where the reaction should occur very rapidly [ 43 ], it may be possible that the obtained results are due to the mentioned interactions between large graphene oxide platelets and luciferase, which inhibited the oxidation of luciferin, or between the luciferin and GO.…”
Section: Discussionmentioning
confidence: 99%
“…In that work, although using two different in vitro approaches (such as the differentiated HepaRG™ cells for monitoring CYP gene expression and a microsomal-based model for assessing CYP metabolic activity), it has been reported a strong reduction of transcription of many CYP isoforms (CYP3A4, CYP2B6, CYP1A2, and CYP2E1) and the inhibition of the catalytic activity of CYP3A4, CYP1A2, and CYP2D6 by GO ( Strojny et al, 2018 ). Similarly, Sekretarska et al showed, using a microsomal-based model, that GO (50 and 100 μg/ml) caused inhibition of CYP2C9 catalytic activity higher than 40% compared to the control, but, in HepG2 cells, GO did not affect the relative gene expression ( Sekretarska et al, 2019 ). It is worthwhile mentioning that the presented data on CYP gene expression and metabolic activity were obtained using the same cell model and, hence, provided for the first time a complete description of the CYP-inhibition effect of GO in functional, differentiated hepatocytes.…”
Section: Discussionmentioning
confidence: 94%
“…There is also evidence that HepG2 cells have low expression of CYP2C9, an important enzyme involved in drug metabolism [44][45][46]. This low expression affects their suitability as a model for studying hepatotoxicity and drug metabolism [47,48]. It is important to consider this limitation when using HepG2 cells as a model system for drug metabolism research.…”
Section: Discussionmentioning
confidence: 99%